Solar‐blind AlxGa1–xN MSM photodetectors on patterned AlN/sapphire templates with 0.4 < x < 1. Issue 3 (4th February 2014) - Knigge, A.; Brendel, M.; Brunner, F.; Einfeldt, S.; Knauer, A.; Kueller, V.; Zeimer, U.; Weyers, M.
Abstract: Solar‐blind Schottky‐type metal‐semiconductor‐metal (MSM) photodetectors (PDs) based on Alx Ga1–x N absorber layers with x varying between 0.4 and 1 are investigated. The impact of the epitaxial lateral overgrowth (ELO) technique on stripe patterned AlN/sapphire templates is evaluated by comparing devices on ELO as well as planar AlN/sapphire templates. Device characteristics have been found to depend on the orientation of the finger‐electrodes with respect to the stripe pattern. The responsivity of ELO PDs with finger‐electrodes perpendicular to the stripes is higher than that for the parallel case or for PDs on planar templates. For x ≥ 0.9 an enhancement of about 50% and for x = 0.4 of more than two orders of magnitude due to photoconductive gain are observed. The orientation dependence is explained by a non‐uniform dislocation density on the ELO template, involving channels of low dislocation density. Additionally, the Al/Ga incorporation is found to be non‐uniform, particularly for low values of x. Due to the absence of photoconductive gain for x ≥ 0.9, the gain observed for x = 0.4 using ELO templates with perpendicular finger orientation is attributed to compositional modulation of the absorber layer. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)